Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward and Peppard pada Kantor Pertanahan Kabupaten Klungkung - Sugiyanti, Ni Putu Happy Valentina; Sariyasa, Sariyasa; Sunarya, I Made Gede (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The Klungkung Regency Land Office (Kantah Klungkung) is responsible for fifteen (15) main activities and focuses on tasks related to land services. There are only 23 Functional Officials out of the 127 people needed based on agency workload analysis. Apart from that, data from each section cannot be utilized properly because the system is not yet integrated. As a result, to ensure sustainable IS/IT growth in Kantah Klungkung and support the implementation of the Integrity Zone, a strategic plan for information systems is needed. This study chose Ward and Peppard's framework because they have adequate tools, are flexible, and can be used with existing business process strategic plans. Through the IFAS and EFAS questionnaires, four components of SWOT analysis were found. According to the results of internal SWOT analysis and external analysis of the business environment with Value Chain. As a result, with a SWOT quadrant score on the x-axis of 0.76 and the y-axis of 0.61, the company has the ability to maximize existing strengths and opportunities. This research produces a map of application requirements, recommendations for infrastructure improvements, and the number of workers needed by IS/IT managers over five years.